CONCEPTUAL MODEL OF INTEGRATION OF BUSINESS FUNCTIONS ON INTERNAL BUSINESS PROCESS PERFORMANCE - Yulianto, Erwin; Sudirman, Iman; Sutarman, Sutarman; Setiawan, Awan (TRIKONOMIKA, 2023)
The trend of banking performance in the last five years is still fluctuating. One of the root causes is measured from a Balanced Scorecard perspective, namely the not yet optimal integration of business functions in the Internal Business Process. The continuous development of systems, information and communication technology has profound implications for the integration of business functions such as sales and marketing, procurement, finance and accounting, research and development of banking products/services. This study aims to identify, examine and analyze empirical evidence on phenomena that occur in the banking world so that research hypotheses are generated to be studied and tested using quantitative methods in order to obtain dominant variables that influence as the basis for developing a measurable conceptual model.